Adapted Conservation Agriculture Practices Can Increase Energy Productivity and Lower Yield-Scaled Greenhouse Gas Emissions in Coastal Bangladesh - Krupnik, Timothy J.; Hossain, Md. Khaled; Timsina, Jagadish; Gathala, Mahesh K.; Sapkota, Tek B.; Yasmin, Samina; Shahjahan, Md.; Hossain, Farhad; Kurishi, Alanuzzaman; Miah, Azahar Ali; Rahman, B. M. Saidur; McDonald, Andrew J. (Frontiers in Agronomy, 2022)
While numerous studies have documented the benefits of conservation agriculture (CA) in South Asia, most focus on favorable environments where farmers have reliable access to energy supporting irrigation and inputs. The performance of CA in south Asia’s under-developed coastal environments are comparatively understudied. In these environments, farmers are increasingly interested in growing a second crop to meet food security and income generation objectives in rotation following the predominant monsoon season rice crop, though labor, energy costs, and investment constraints limit farmers’ ability to do so. We hypothesized that rotating rice with maize using complete CA (i.e., strip-tilled maize followed by unpuddled transplanted rice), or adapted CA (ACA, i.e., strip-tilled maize followed by fully-tilled, puddled rice with residues retained across rotations) would reduce costs and energy use, increase energy-use efficiency, and reduce yield-scaled CO2-eq. emissions (YSE) and total global warming potential (GWP) in Bangladesh’s coastal deltaic environment. Starting with winter maize followed by summer rice, we evaluated four tillage and crop establishment (TCE) treatments in farmer-managed experiments in partially irrigated and rainfed environments over three years in 40 farmer’s fields across Bangladesh’s coastal districts. Treatments included farmers’ own practices (FP), conventional full-tillage (CT), complete CA, and ACA. Complete CA and ACA were significantly more energy-efficient and energy-productive than FP or CT. The order of YSE in rice was CA< CT or FP < ACA while in maize, it was CA or ACA < FP < CT, and at the systems level was CA < ACA < FP < CT. Across environments, complete CA and ACA resulted in 15-18% higher systems yield, 26-40% less manual labor, 1-12% and 33-35% reduced total production and TCE costs, 26-51% and 27-72% higher total benefits and value-cost ratio, 13-17% greater grain energy output, and 2-18% lower YSE, compared to CT and FP. While our data suggest that both complete CA and ACA can result in a range of positive agronomic, economic, and environmental outcomes compared to FP or CT, post-trial surveys and discussions with farmers revealed a strong practical aversion to use of the full suite of CA practices and preference for adapted practices.